Short-term monitoring of fiscal policy discipline - Gonzalo Camba-Méndez; Ana Lamo (European Central Bank (ECB), 2002)
Under the Maastricht Treaty and the Stability and Growth Pact (SGP) European Union (EU) Member States commit themselves to avoid excessive deficits over 3% of GDP and to pursue the medium-term objective of budgetary positions close to balance or in surplus. The SGP provides also regulation for the surveillance of budgetary positions. An analysis of associated tools is the focus of this paper. In particular, it addresses two open issues in the empirical public finance literature which are crucial for monitoring fiscal policy discipline in the EU. First, the estimation of the structural component of the fiscal balance ratio. Second, the computation, when only annual fiscal data is available, of quarterly budget balance ratios, using relevant information from quarterly measured macroeconomic series. An econometric model that addresses both issues is presented and estimated. Additionally, this modelling framework allows us to answer questions such as: what is the safety margin that will prevent a particular country from reaching with certain probability abudget deficit that breaches the 3% upper bound?
Keywords: C32; E60; H62; 330; Interpolation; State Space Modelling; Structural Deficit Ratio